WLE/IWMI support for updated groundwater policies and implementation programs in Laos has led to new policies and investments for sustainable groundwater management - CGIAR Research Program on Water, Land and Ecosystems (2021)
Since 2019, when WLE/IWMI reported on the impact of its research on groundwater knowledge generation and management in Laos, policies and investment programs have evolved that are benefitting groundwater-dependent communities. There is now greater recognition of the strategic importance of groundwater, and more emphasis placed on the systematic management of groundwater by responsible government agencies and in development projects. In particular, WLE/IWMI-facilitated knowledge and capacity development are helping Laos establish a national groundwater roadmap and sub-national groundwater management plans.